Evidence of genotype-environment interaction for final live weight in the performance test of the Cuban Zebu - Rodr?guez, Yusleiby; Guerra, Danilo (Cuban Journal of Agricultural Science, 2013)
The response of 203 Cuban Zebu sires was evaluated from the final live weight in the performance test of their offspring, born in the period 1981-2009, in six Cuban cattle breeding enterprises. The breeding value of the sires was compared, depending on the environment where their offspring realized the test (high or low). These two levels were defined from the mean value of the gain in test to the corresponding group of contemporaries. For each one of the two data file an animal model was analyzed including the random effect of the animal, final age of the test, as linear covariable, and the fixed effect of the contemporary group (enterprise-year-birth trimester). In both groups the Spearman and Pearson correlations were determined to the breeding values of the sires. Heritability values from moderate to low were obtained in both cases (h2 = 0.22 ? 0.04 in the high environmental group and h2 = 0.15 ? 0.03 in the low). The values of Spearman and Pearson correlations (0.39 and 0.46, respectively) indicate that there is genotype x environmental group interaction between these extreme environments. Thus, the male offspring from sires of high breeding value do not perform in the same way when the environmental or management conditions change. In the national genetic improvement plan of Cuban Zebu, it is recommended to consider the selective use of sires according to the characteristics where their progeny will be developed. Key words: Cuban Zebu, genotype-environment interaction, growth, robust, plastic